The anti-surfactant effect of silane on the facets-controlled growth of GaN nanorods by MOCVD. (August 2016) - Li, J.Z.; Chen, Z.Z.; Li, S.F.; Jiao, Q.Q.; Feng, Y.L.; Jiang, S.X.; Chen, Y.F.; Yu, T.J.; Shen, B.; Zhang, G.Y.
Abstract: N-polar GaN nanorods were selective area grown by continuous mode metalorganic chemical vapor deposition (MOCVD) under a Ga-rich and high silane flow condition. The interruption comparing with continuous supply of silane flow was performed to study the role of silane flux. High resolution scanning electron microscopy (SEM), x-ray diffraction (XRD), cathodoluminescence (CL) and x-ray photoelectron spectroscopy (XPS) measurements were performed. The enhanced vertical growth rate was achieved as 42 μm/h and sharp smooth m-plane, r-plane and c-plane facets were obtained for the nanorods with high silane flux. SiN bonds were clarified to be formed on the surface of the nanorod by XPS spectra. The silane acting as anti-surfactant was suggested to explain the diffusion and incorporation of the species on the facets of GaN nanorods. Highlights: The enhanced vertical growth rate was achieved to 42 μm/h for the GaN nanorods with high silane flux. Silane flux improved the nanorods properties by enhancing the edge emission and suppressing the yellow luminescence. The silane acting as anti-surfactant was suggested to explain the facets-controlled of GaN nanorods.